Frontispiece: Single‐Site Active Cobalt‐Based Photocatalyst with a Long Carrier Lifetime for Spontaneous Overall Water Splitting. Issue 32 (27th July 2017) - Liu, Wei; Cao, Linlin; Cheng, Weiren; Cao, Yuanjie; Liu, Xiaokang; Zhang, Wei; Mou, Xiaoli; Jin, Lili; Zheng, Xusheng; Che, Wei; Liu, Qinghua; Yao, Tao; et al.
Abstract : Water Splitting In their Communication onpage 9311 ff., T. Yao, S. Q. Wei et al. show that Co‐P4 single sites confined on polymeric g‐C3 N4 give rise to a single‐site photocatalyst for spontaneous overall water splitting.